Happy hippo, angry duck : a book of moods - Boynton, Sandra (New York : Little Simon, 2011)
Clever animals exemplify a wide range of emotions in this hilarious story about different feelings.
On board pages.
Keywords: Animals -- Juvenile fiction; Board books; Emotions -- Juvenile fiction; Emotions -- Fiction; Animals -- Fiction; Board books for children; Emotions -- Fiction